EVALUATION OF CARDIOPROTECTIVE ACTIVITY OF ALLIUM CEPA AERIAL LEAVES - M., Jalaiah; R., Sarvanan; H., Gowtham C.; Y., Vinay; Y., Akhila (International Journal of Current Pharmaceutical Research, 2017)
Objective: The present work deals with the study of the ethanolic extract of fruits of Allium cepa aerial leaves for cardioprotective activity. Methods: Cardioprotective activity of the ethanolic extract of aerial leaves of Allium cepa was determined by the administration of isoproterenol (60 mg/kg, s. c) for two days. Results: Pretreatment with ethanolic extract of Allium cepa aerial leaves (200 mg/kg, p. o and 100 mg/kg, p. o) for 28 d in significantly (p<0.01) reduce the levels of serum transaminases, alkaline phosphates, lactate dehydrogenase, creatinine kinase, total cholesterol, triglycerides, LDL-cholesterol, VLDL-cholesterol and increase the levels of HDL-cholesterol. Histopathological studies of the hearts of isoproterenol treated rats have showed infiltration of inflammatory cells and lacking of continuity in muscle fiber was suggesting an irreversible cell injury. Conclusion: Animals treated with ethanolic extract of Allium cepa aerial leaves showed less degenerative changes compared to isoproterenol-treated animals.